The Effect of Self-Employment on Health: Evidence from Longitudinal Social Security Data - Judite Goncalves; Pedro S. Martins (Institute of Labor Economics (IZA), 2018)
The growth of novel flexible work formats raises a number of questions about their effects upon health and the potential required changes in public policy. However, answering these questions is hampered by lack of suitable data. This is the first paper that draws on comprehensive longitudinal administrative data to examine the impact of self-employment in terms of health. It also considers an objective measure of health – hospital admissions – that is not subject to recall or other biases that may affect previous studies. Our findings, based on a representative sample of over 100,000 individuals followed monthly from 2005 to 2011 in Portugal, indicate that the likelihood of hospital admission of self-employed individuals is about half that of wage workers. This finding holds even when accounting for a potential self-selection of the healthy into self-employment. Similar results are found for mortality rates.
Keywords: I18; J24; 330; self-employment; hospitalization; sick leave; mortality